An international multi-institutional validation of T1 sub-staging of intraductal papillary mucinous neoplasm-derived pancreatic cancer - Habib, Joseph; Rompen, Ingmar F.; Campbell, Brady A.; Andel, Paul C. M.; Kinny-Köster, Benedict; Damaseviciute, Ryte; Brock Hewitt, D.; Sacks, Greg D.; Javed, Ammar A.; Besselink, Marc G.; van Santvoort, Hjalmar C.; Daamen, Lois A.; et al. (Journal of the National Cancer Institute, 2024)
Intraductal papillary mucinous neoplasm (IPMN)-derived pancreatic ductal adenocarcinoma (PDAC) is resected at smaller sizes compared with its biologically distinct counterpart, pancreatic intraepithelial neoplasia (PanIN)-derived PDAC. Thus, experts proposed T1 sub-staging for IPMN-derived PDAC. However, this has never been validated.Consecutive upfront surgery patients with IPMN-derived PDAC from 5 international high-volume centers were classified by the proposed T1 sub-staging classification (T1a ≤0.5, T1b >0.5 and ≤1.0, and T1c >1.0 and ≤2.0 cm) using the invasive component size. Kaplan-Meier and log-rank tests were used to compare overall survival (OS). A multivariable Cox regression was used to determine hazard ratios (HRs) with confidence intervals (95% CIs).Among 747 patients, 69 (9.2%), 50 (6.7%), 99 (13.0%), and 531 patients (71.1%), comprised the T1a, T1b, T1c, and T2-4 subgroups, respectively. Increasing T-stage was associated with elevated CA19-9, poorer grade, nodal positivity, R1 margin, and tubular subtype. Median OS for T1a, T1b, T1c, and T2-4 were 159.0 (95% CI = 126.0 to NR), 128.8 (98.3 to NR), 77.6 (48.3 to 108.2), and 31.4 (27.5 to 37.7) months, respectively (P < .001). OS decreased with increasing T-stage for all pairwise comparisons (all P < .05). After risk adjustment, older than age 65, elevated CA19-9, T1b [HR = 2.55 (1.22 to 5.32)], T1c [HR = 3.04 (1.60 to 5.76)], and T2-4 [HR = 3.41 (1.89 to 6.17)] compared with T1a, nodal positivity, R1 margin, and no adjuvant chemotherapy were associated with worse OS. Disease recurrence was more common in T2-4 tumors (56.4%) compared with T1a (18.2%), T1b (23.9%), and T1c (36.1%, P < .001).T1 sub-staging of IPMN-derived PDAC is valid and has significant prognostic value. Advancing T1 sub-stage is associated with worse histopathology, survival, and recurrence. T1 sub-staging is recommended for future guidelines.
Online veröffentlicht: 19. Juli 2024
Gesehen am 18.08.2025